The Effect of Work Commitment and Teacher Certification on the Quality of State High Schools in Palembang City - Asni Asni; Edi Harapan; Syaiful Eddy (International Journal of Educational Technology and Society, 2025)
Quality schools are the goal of every educational institution, therefore it is important to pay attention to various aspects which are believed to influence school quality. This research was conducted with the aim of examining the influence of work commitment and teacher certification on school quality (State High School in Palembang City). The method used in this research is a quantitative method, with data obtained through questionnaires and documentation. The data obtained from the research process was then analyzed quantitatively through statistical computing (t test and F test). The results of the research conducted state that work commitment has a positive and significant effect on school quality; teacher certification has been proven to make a positive and significant contribution to school quality; In simultaneous testing it was found that work commitment and teacher certification affected the quality of State High Schools in Palembang City. The contribution of the two independent variables to the dependent variable is in the quite high category